Genetika dan Farmakogenomika untuk Kinerja Atletik: Tren Terkini dan Arah Masa Depan di ASEAN - Nugraha, Afif Tri; Malau , Jekmal; Kasasiah , Ahsanal; Aprillia, Cantika; Ainaputri, Aliza Salsabila; Siboro , Dewi Pratiwi Purba (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The integration of sport genomics and pharmacogenomics has become a central pillar of precision sports medicine, enabling individualized training, nutrition, and medication/supplement strategies for athletes. This structured narrative review synthesizes literature published between 2015 and 2025 from PubMed, ScienceDirect, and Google Scholar, with particular emphasis on implementation relevance in ASEAN, especially Indonesia. Findings are organized into three major themes: (1) genetic contributions to strength and endurance phenotypes, body composition, recovery, and injury susceptibility; (2) pharmacogenomic implications for drug selection, dose optimization, therapeutic safety, and potential exercise with drug interactions (e.g., NSAIDs, inhaled bronchodilators, caffeine, and creatine); and (3) ethical, privacy, equity, and gene-doping considerations. Athletic performance is inherently polygenic; variants in genes such as ACTN3, ACE, PPARGC1A, PPARA, and VEGF-A contribute to the power–endurance spectrum and vascular–metabolic adaptation, while pharmacogenes including CYP2C9, CYP1A2, ADORA2A, and ADRB2 may modulate therapeutic efficacy and adverse-effect risk. Moreover, physical activity itself may influence drug metabolism and pharmacodynamic responses, underscoring the limitations of one-size-fits-all protocols. Overall, genetic information should be positioned as a complementary decision-support layer rather than a deterministic predictor in sports medicine practice. Strengthening implementation in ASEAN requires larger, well-characterized athlete cohorts, standardized marker panels, longitudinal data integration, and robust ethical–regulatory frameworks to ensure safe and evidence-based genomic application.